Forward vehicle collision mitigation by braking system based on artificial bee colony algorithm. Issue 7 (October 2016) - Yousef, Qais; Alqudah, Amin; Alboon, Shadi
Abstract Decision-making is a crucial step in vehicles' safety systems, which determines the right time for the system to intervene and to take the required action, depending on the current situation of the vehicle. The warning/intervention system becomes active when the driving situation considered unpleasant while still giving the control to the driver. Taking the action of warning, braking and determining the best time for this intervention are important decisions in collision mitigation systems. In this work, a novel system is designed based on artificial bee colony algorithm to enhance the decision-making in such systems. This work c oncentrates on collision mitigation by braking systems only, for front-to-rear accidents. This paper studies cases when the hosting vehicle approaches moving and stationary objects. This work is simulated, and the results are obtained and analyzed which proved the contribution to this work in reducing the collision speed and the stopping distance, in comparison with previous related works.